Analisis Besar Iuran Normal Metode Frozen Initial Liability dan Metode Entry Age Normal Menggunakan Tingkat Suku Bunga Cox-Ingersoll-Ross (CIR) - Mahrani, Dwi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2023)
One form of social security program is a pension funding program. A pension plan is a program designed to provide benefits to employees when they retire. Based on the type of membership, the pension program is divided into 2 types, namely individuals and groups. There are differences in the methods used for the two types of participation, namely the Normal Entry Age (EAN) method for individual pension programs and the Frozen Initial Liability (FIL) method for group pension programs. Each period, both individual and group pension program participants are required to pay normal contributions. Things that influence the amount of normal contributions for each worker are the age at which they enter work, the participant's initial salary, and the participant's chance of survival/death. In addition, the calculation of normal contributions also depends on the interest rate used. In this study, the interest rate used is the interest rate of the Cox-Ingersoll-Ross (CIR) model. The normal contribution amount for EAN is constant for each period, while the normal contribution amount for FIL changes when there are participants who retire in the pension program group. The normal FIL contribution tends to be on average compared to the EAN normal contribution for each participant.